1996
DOI: 10.1007/bf00807325
|View full text |Cite
|
Sign up to set email alerts
|

Plasma amino acids in four models of experimental liver injury in rats

Abstract: We studied the plasma amino acid profiles in four models of hepatic injury in rats. In partially hepatectomized rats (65% of liver was removed) we observed significant increase of aromatic amino acids (AAA; i.e. tyrosine and phenylalanine), taurine, aspartate, threonine, serine, asparagine, methionine, ornithine and histidine. Branched-chain amino acids (BCAA; i.e. valine, leucine and isoleucine) concentrations were unchanged. In ischemic and carbon tetrachloride acute liver damage we observed extreme elevatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 16 publications
2
42
0
Order By: Relevance
“…Marked increases in AST, ALT and LDH as markers of hepatic injury indicate that serious and acute liver damage occurred. These observations suggest that a large amount of the arginase contained in the liver is likely to have leaked out into the circulating blood and led to the conversion of arginine to ornithine [10,11]. Exposure to hypoxia, however, resulted in no change in the levels of these marker enzymes compared to normoxic controls, suggesting that hepatic injury had not occurred under the hypoxic conditions used.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Marked increases in AST, ALT and LDH as markers of hepatic injury indicate that serious and acute liver damage occurred. These observations suggest that a large amount of the arginase contained in the liver is likely to have leaked out into the circulating blood and led to the conversion of arginine to ornithine [10,11]. Exposure to hypoxia, however, resulted in no change in the levels of these marker enzymes compared to normoxic controls, suggesting that hepatic injury had not occurred under the hypoxic conditions used.…”
Section: Discussionmentioning
confidence: 46%
“…In the current study, acute hepatic injury induced by a single administration of CCl 4 resulted in an elevation in both the levels of BCAAs and AAAs and significant decrease in the Fischer ratio. Holecek et al [10] reported that the Fischer ratio remained unaffected by acute liver damage, in contrast to the reported response to liver cirrhosis. The reason for difference between their and our results may be attributed to the severity of liver damage, as judged by amino acid levels and activities of marker enzymes in liver injury.…”
Section: Discussionmentioning
confidence: 75%
“…Acute injury or the decompensation of a previously wellcompensated liver disease result in a marked increase in aminoacidemia, including the BCAA, due to the leak of amino acids from dying hepatocytes into the circulation [40,41,[65][66][67]. On the other hand, in the recovery phase after acute liver injury in rats we observed a decrease in a group of amino acids in blood plasma, including the BCAA, below the control values [67].…”
Section: The Role Of the Type Of Liver Failurementioning
confidence: 91%
“…The decrease of plasma BCAA levels is a hallmark of liver cirrhosis [40,41] and it might be suggested that the favorable effects of BCAA supplementation on hepatic encephalopathy, protein balance, glucose tolerance, immunity, and liver functions reported in a number of studies result mostly (if not entirely) from corrections of disadvantages resulting from their deficiency. Therefore, theoretically, BCAA supplementation might be of benefit particularly in patients with low BCAA levels.…”
Section: Bcaa Deficiency and Therapeutic Effectiveness Of The Bcaamentioning
confidence: 99%
“…However, a serious problem in many trials evaluating the effectiveness of BCAA is the lack of information about alterations in aminoacidemia. An increase in BCAA levels has been observed in acute injury or in the case of acute decompensation of liver disease (Rosen et al 1977; Hehir et al 1985; Holecek et al 1996a; Holecek et al 1999). …”
Section: Therapeutic Perspectivesmentioning
confidence: 99%